PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PRACTICE REHERSAL PAIRS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 17 PADANG - Dewita, Ria; Febriana, Rina; Lovia, Lita (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was motivated because students skill to share information in learning or exercises not well and students understanding of mathematical conceptual are low. This research aims to determine whether students understanding of mathematical conceptual with implementing active learning Practice Rehearsal Pairs type better than understanding of the mathematical conceptual of the conventional learning in class VII SMPN 17 Padang. This was an experimental research which used random research design toward the subject. The instrument used in this research is a test in students understanding on mathematics concept. Based on the result of data analysis, it was revealed that the sample was distributed normally and had homogeny variant. Hypothesis test results obtained t=3,27 was bigger than ,Â  indicating that the hypothesis was accepted. So, it was concluded that the application of active learning Practice Rehearsal Pairs type could improve the students understanding on mathematics conceptual better than the conventional one.